NaOH and Ensila plus additives for wheat silage and alfalfa haylage for growing steers - Bolsen, K.; Ilg, H.; Nuwanyakpa, M. (Kansas State University. Agricultural Experiment Station, 2011)
Enzyme (Ensila Plus) and alkali (NaOH) silage additives were evaluated with whole-plant wheat silages which were fed with or without alfalfa haylage (45% moisture). Steers fed NaOH silage consumed the most feed but were the least efficient. Although adding haylage increased feed intake, daily gain was not improved. Ensila Plus wheat silage was used 5.2% more efficiently than control wheat silage. NaOH increased ensiling temperatures by 5 to 80 C during the 4-week ensiling period. The amount of silage dry matter removed from the silos and fed was unusually low for all three wheat silages (77.6,79.4, and 77.1% for control, Ensila Plus, and NaOH silages, respectively).
Keywords: Beef; Alkali; Ensila Plus; Wheat silage; Alfalfa silage; Steers